1963
DOI: 10.1128/jb.86.5.1084-1097.1963
|View full text |Cite
|
Sign up to set email alerts
|

Serology of the Soluble Antigens of the Pathogenic Clostridia

Abstract: ELLNER, PAUL D. (University of Vermont, Burlington), AND STANLEY S. GREEN. Serology of the soluble antigens of the pathogenic clostridia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1963
1963
1991
1991

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Band splitting was produced only when wells containing extracts of the homologous system were bordered by wells containing extracts of related organisms. The cause of the band splitting is obscure at present, but a similar phenomenon has been found with other bacteria (1,4). Possibly the heterologous strain possesses a different concentration of a specific antigenic determinant than does the homologous strain which (i) tends to enhance the formation of a band previously not visible or (ii) causes a band to split away from an apparent homogeneous band due to attractive forces.…”
Section: Downloaded Fromsupporting
confidence: 53%
“…Band splitting was produced only when wells containing extracts of the homologous system were bordered by wells containing extracts of related organisms. The cause of the band splitting is obscure at present, but a similar phenomenon has been found with other bacteria (1,4). Possibly the heterologous strain possesses a different concentration of a specific antigenic determinant than does the homologous strain which (i) tends to enhance the formation of a band previously not visible or (ii) causes a band to split away from an apparent homogeneous band due to attractive forces.…”
Section: Downloaded Fromsupporting
confidence: 53%
“…The soluble antigens employed were the same as were used in the previous study (Ellner and Green, 1963). All methods pertaining to cultures, antigen production, immunization of animals, and agar gel diffusion have been described.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study of the soluble antigens of the ten species of clostridia most frequently involved in human infections (Ellner and Green, 1963) disclosed that, although extreme heterogeneity occurs, a number of these species possess specific antigens, when examined by agar gel diffusion. Although cross-reactions among these species are frequent, subsequent investigations with specifically absorbed globulins in some cases have demonstrated that it is possible to identify the soluble antigens of these organisms.…”
mentioning
confidence: 99%
“…3.3 1.4 1.1 9.4 22.8 0.8 2.5 5.5 14.8 2.6 11.4 1.3 2.7 2.3 2.1 1.5 6.2 8.3 Hobb's 8 0.7 1.8 0.6 9.8 32.4 0.9 1.7 2.5 15.7 2.8 7.5 0.9 1.3 4.5 3.6 1.7 3.6 8.0 Hobb's ll 1.1 0.9 0.5 6.8 24.3 1.4 2.1 3.6 20.0 3.0 13.2 4.2 1.6 T 5.7 1.0 3.8 6.8 Hobb's 13 1.3 0.6 T 6.8 22.5 1.5 1.4 2.6 21.0 2.7 13.5 3.4 1.9 3.9 3.9 1.3 6.3 5.4 Hobb's 7 1.3 1.6 0.9 15.9 25.2 4.0 0.5 1.9 17.6 2.3 7.4 1.8 2.7 1.6 2.4 1.6 3.41 7.9 a See footnote a of Table 1. b Average, 7.2. c See footnote c of Table 1. d T designates trace amount (less than 0.5%). Table 3.…”
Section: A37mentioning
confidence: 99%
“…have been used by some workers (5, 11), serological and immunological studies by some (3,6,7,13,18,21), and enzymatic studies by others (12,19).…”
mentioning
confidence: 99%